2011
DOI: 10.1002/ibd.21526
|View full text |Cite
|
Sign up to set email alerts
|

Relative role of methylator and tumor suppressor pathways in ulcerative colitis-associated colon cancer

Abstract: Unlike other inflammatory gastrointestinal cancers, colitis-associated colorectal cancers do not preferentially arise via a methylator pathway when compared to sporadic colorectal cancers. Chromosomal instability remains an important etiology, but with a unique p53 frequency and mutation pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
6
20
0
Order By: Relevance
“…19,20,21 Our current study showed that 36.4% of pouch adenocarcinomas and 61.1% of UCassociated adenocarcinomas had p53 nuclear immunoreactivity, indicating that p53 abnormality occurs during the tumorigenesis of both neoplasms, consistent with previous studies. 11,22 In the current study, only few cases of pouch and UC-associated adenocarcinoma showed nuclear accumulation of b-catenin, suggesting that loss of APC function may not play a key role in the pathogenesis of either of these processes, in line with the results from a previous study. 11 Epigenetic DNA modification by methylation (known as CIMP-high) has also been shown to play a significant role in tumorigenesis in 20% of colorectal cancers, 7 However, a recent study by Sanchez et al 22 reported that 5% of UC-associated cancers had CIMP-high.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…19,20,21 Our current study showed that 36.4% of pouch adenocarcinomas and 61.1% of UCassociated adenocarcinomas had p53 nuclear immunoreactivity, indicating that p53 abnormality occurs during the tumorigenesis of both neoplasms, consistent with previous studies. 11,22 In the current study, only few cases of pouch and UC-associated adenocarcinoma showed nuclear accumulation of b-catenin, suggesting that loss of APC function may not play a key role in the pathogenesis of either of these processes, in line with the results from a previous study. 11 Epigenetic DNA modification by methylation (known as CIMP-high) has also been shown to play a significant role in tumorigenesis in 20% of colorectal cancers, 7 However, a recent study by Sanchez et al 22 reported that 5% of UC-associated cancers had CIMP-high.…”
Section: Discussionsupporting
confidence: 91%
“…11,22 In the current study, only few cases of pouch and UC-associated adenocarcinoma showed nuclear accumulation of b-catenin, suggesting that loss of APC function may not play a key role in the pathogenesis of either of these processes, in line with the results from a previous study. 11 Epigenetic DNA modification by methylation (known as CIMP-high) has also been shown to play a significant role in tumorigenesis in 20% of colorectal cancers, 7 However, a recent study by Sanchez et al 22 reported that 5% of UC-associated cancers had CIMP-high. However, CIMP has not been examined in our study, as tissue from 35.7% of cases had been fixed in Hollande solution.…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to note that the method of carcinogenesis in IBD has been shown in several studies to be distinct from sporadic CRC. 15,16 Further evaluation of the differences in epigenetic changes in CRC among this population are necessary. Previous reports have suggested that a limited resection in IBD-associated CRC may be associated with a greater risk of cancer-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that EGFR inactivation increases tumor progression across multiple tumor types during inflammation, despite differential activation of either the MAPK or Wnt pathway. There is currently debate about whether there are aberrant signaling pathways specific to CAC versus sporadic colorectal adenocarcinoma (41,42), and further clinical studies are warranted to determine the molecular basis of these disparate tumor types. Nevertheless, we have identified ERK1/2 activation as a consistent molecular characteristic of Il10 -/-colorectal tumors, suggesting a potential role for dysregulation of the MAPK pathway in CAC patients with chronic inflammation, which merits further investigation.…”
Section: Figurementioning
confidence: 99%
“…However, EGFR inhibition is not universally efficacious, and resistance to EGFR inhibition occurs in tumors with mutant BRAF or KRAS (37)(38)(39)(40). Importantly, these mutations are common in tumors from ulcerative colitis patients (41,42), suggesting possible widespread resistance to EGFR inhibition in this population.…”
Section: Introductionmentioning
confidence: 99%